Spondias Growing in the Florida Home Landscape - Jonathan H. Crane; Jeff Wasielewski (EDIS)
Spondias species (whose common names among English speakers include ambarella, Ataheite apple, mombins, and hog plums) are flowering trees native to tropical and subtropical regions. They are known for their sweet fruit and grow well in the warmest parts of Florida. This revised 8-page fact sheet discusses biology, distribution and uses, as well as guidelines for propagation and maintenance. Written by Jonathan H. Crane and Jeffrey Wasielewski, and published by the UF Department of Horticultural Sciences, April 2015. (Photo by Forest & Kim Starr, CC BY 3.0)